Bahasa Inggris - Dody Hapsoro; Maria Immaculata Bahantwelu (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
This study aims to examine the effect of capital structure on company value with earnings management as a mediating variable. The capital structure is proxied using a debt to equity ratio (DER), company value is proxied using Tobin’s Q and real earnings management is proxied using costs of production activities. The research population is 144 manufacturing companies listed on the Indonesia Stock Exchange (IDX). 204 samples are used in this study. Data used in this study is the secondary data obtained from Indonesia Stock Exchange, contained on www.idx.co.id. The data analysis method used in this study is partial least squares (PLS) method using a WarpPLS 4.0 application. The results of the analysis show that capital structure has a positive effect on company value and real earnings management is proven to partially mediate the effect of capital structure on company value. The results of this study should encourage standard-setting bodies to make stricter regulations on real earnings management practices that tend to cause management to commit fraud.